Early yield and growth performance of Hevea clones evolved by ortet selection from polycross population in Odisha, Eastern India. - Krishan, B. (Rubber Science, 36(2): 2023. 194-198.)
Evaluation of ten ortet clones was carried out in a clonal nursery trial under dry sub-humid conditions of Odisha state in eastern region of India. The ortet clones were assessed for yield based on test tapping, girth and girth increment, bark thickness, first branching height and number of primary branches. Ortet clones O 3 and O 4 recorded high annual yield of 114.8 g t-1 10t-1 and 116.4 g t-1 10t-1 respectively over three years. On the basis of pooled yield, two ortet clones viz. O 3 and O 4 were found superior to RRIM 600, IRCA 111, SCATC 93-114 and comparable with RRII 208, the clone recommended for eastern India. Five ortet clones viz. O 3, O 4, O 5, O 8 and O 10 had better girth and girth increment. Clones O 3, O 4 and O 10 recorded high bark thickness. Clones O 3, O 4 and O 8 recorded high branching height. Four ortet clones viz. O 3, O 4, O 7 and O 10 were found superior in terms of yield and growth. These selections will be subjected to further large scale evaluation.
Keywords: Clones; Girth; Ortets; Polycross; Test tap; Yield